Different modulation pattern of spinal stretch reflex excitability in highly trained endurance runners - Ogawa, T.; Kawashima, N.; Suzuki, S.; Nakazawa, K. (European Journal of Applied Physiology, 2012)
This study was undertaken to elucidate the impact of long-term physical training on the modulation of stretch reflex excitability. To this end, electromyographic activities of the soleus muscle in response to quick toe-up rotation were compared between highly trained endurance runners (n = 8) and non-trained control subjects (n = 9). We specifically focused on the stretch reflex modulation under different voluntary activation levels, from rest to pre-activated conditions (5, 10, 20, and 30% of the maximal). While the two groups showed similar modulation patterns of the stretch reflex responses, the extent of reflex modulation in accordance with the muscle pre-activation level was larger in the trained group. The present results therefore suggest a different modulation pattern of the stretch reflex responses with changing activation level between individuals with different physical background, and the enhancement of the responses in the trained individuals may particularly be advantageous in exerting high level muscle contraction.